Campylobacter jejuni Surface-Bound Protease HtrA, but Not the Secreted Protease nor Protease in Shed Membrane Vesicles, Disrupts Epithelial Cell-to-Cell Junctions - Sharafutdinov, Irshad; Tegtmeyer, Nicole; Rohde, Manfred; Olofsson, Annelie; Rehman, Zia ur; Arnqvist, Anna; Backert, Steffen (Cells, 2024)
Fundamental functions of the intestinal epithelium include the digestion of food, absorption of nutrients, and its ability to act as the first barrier against intruding microbes. Campylobacter jejuni is a major zoonotic pathogen accounting for a substantial portion of bacterial foodborne illnesses. The germ colonizes the intestines of birds and is mainly transmitted to humans through the consumption of contaminated poultry meat. In the human gastrointestinal tract, the bacterium triggers campylobacteriosis that can progress to serious secondary disorders, including reactive arthritis, inflammatory bowel disease and Guillain–Barré syndrome. We recently discovered that C. jejuni serine protease HtrA disrupts intestinal epithelial barrier functions via cleavage of the tight and adherens junction components occludin, claudin-8 and E-cadherin. However, it is unknown whether epithelial damage is mediated by the secreted soluble enzyme, by HtrA contained in shed outer-membrane vesicles (OMVs) or by another mechanism that has yet to be identified. In the present study, we investigated whether soluble recombinant HtrA and/or purified OMVs induce junctional damage to polarized intestinal epithelial cells compared to live C. jejuni bacteria. By using electron and confocal immunofluorescence microscopy, we show that HtrA-expressing C. jejuni bacteria trigger efficient junctional cell damage, but not soluble purified HtrA or HtrA-containing OMVs, not even at high concentrations far exceeding physiological levels. Instead, we found that only bacteria with active protein biosynthesis effectively cleave junctional proteins, which is followed by paracellular transmigration of C. jejuni through the epithelial cell layer. These findings shed new light on the pathogenic activities of HtrA and virulence strategies of C. jejuni.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Campylobacter; E-cadherin; occludin; serine protease HtrA; tight junctions